2019
DOI: 10.3389/fmicb.2019.01407
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Cand. Patescibacteria in Groundwater Is Caused by Their Preferential Mobilization From Soils and Flourishing Under Oligotrophic Conditions

Abstract: Despite the widely observed predominance of Cand . Patescibacteria in subsurface communities, their input source and ecophysiology are poorly understood. Here we study mechanisms of the formation of a groundwater microbiome and the subsequent differentiation of Cand . Patescibacteria. In the Hainich Critical Zone Exploratory, Germany, we trace the input of microorganisms from forested soils of preferential recharge areas through fractured aquifers along a 5.4 km hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 70 publications
(104 reference statements)
12
116
0
Order By: Relevance
“…Our data suggested that in our fracturedrock ecosystem the alpha diversities of DOM and bacteria were linked. A coupling between the diversities of DOM and bacteria during groundwater recharge could occur as a result of differing processes: (1) combined transport of surface-derived DOM and diverse, allochthonous bacterial communities into the aquifer (Pronk et al, 2006(Pronk et al, , 2009Herrmann et al, 2019).…”
Section: Responses Of the In Situ Biospherementioning
confidence: 99%
“…Our data suggested that in our fracturedrock ecosystem the alpha diversities of DOM and bacteria were linked. A coupling between the diversities of DOM and bacteria during groundwater recharge could occur as a result of differing processes: (1) combined transport of surface-derived DOM and diverse, allochthonous bacterial communities into the aquifer (Pronk et al, 2006(Pronk et al, , 2009Herrmann et al, 2019).…”
Section: Responses Of the In Situ Biospherementioning
confidence: 99%
“…TAG_MAG_00018, from the same phylum (Gracilibacteria class) was in high abundance at TAG (273X) while in low abundance at Rainbow (max 10X; Additional File 4). The predominance of these groups in the Rimicaris holobiont, associated with small genome size for both TAG_MAG_00007 and TAG_MAG_00018 (1,201735 and 841,694 bp, respectively) adds to recent studies showing widespread CPR organisms often in association with abundant autotrophic taxa involved in nitrogen, sulfur and iron cycling [51,52].…”
Section: A Highly Diverse Epibiont Community In Rimicarismentioning
confidence: 62%
“…Also of interest was the presence of conserved bacterial species within the order Absconditabacterales, which are classified under the Patescibacteria phylum. Patescibacteria are unusually small bacteria found in groundwater and produce large surface proteins hypothesized to help them attach or associate with other microorganisms that perform nitrogen, sulfur and iron cycling [29]. The presence of these conserved bacteria suggests that the inflow water seeps originate from groundwater.…”
Section: Resultsmentioning
confidence: 99%